2002
DOI: 10.2460/ajvr.2002.63.579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of dexamethasone and the leukotriene D4 receptor antagonist L-708,738 on lung function and airway cytologic findings in horses with recurrent airway obstruction

Abstract: L-708,738 was bioavailable after oral administration and sustained concentrations in plasma during the dosing period that exceeded in vitro efficacy values. However, airway function did not improve, suggesting that either drug concentrations in the lungs were subtherapeutic or that cysteinyl LT may not be important mediators of airway inflammation in heaves. Results provide the first evidence of cysteinyl LT1 receptors in airways of horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…9,34,35 Furthermore, an LTD 4 -receptor antagonist failed to improve airway function in RAO-affected horses. 36 Overall, these results do not support a role for the cysteinyl-LTs in RAO.…”
Section: Discussionmentioning
confidence: 86%
“…9,34,35 Furthermore, an LTD 4 -receptor antagonist failed to improve airway function in RAO-affected horses. 36 Overall, these results do not support a role for the cysteinyl-LTs in RAO.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have revealed that daily administration of 0.04 mg/kg of dexamethasone to RAO-affected horses maintained in moldy hay environments results in significant improvement in lung function starting on the 3rd day of administration with a maximum benefit by the end of 2 weeks of therapy. 20,21 If horses are maintained in the moldy hay environment, pulmonary function may return to pretreatment levels as early as 6 days after discontinuation of treatment. 20 This could explain the lack of effect of dexamethasone 21-isonicotinate on pulmonary function 10 days after a single injection under these experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 If horses are maintained in the moldy hay environment, pulmonary function may return to pretreatment levels as early as 6 days after discontinuation of treatment. 20 This could explain the lack of effect of dexamethasone 21-isonicotinate on pulmonary function 10 days after a single injection under these experimental conditions. In this study, horses received a microcrystalline insoluble form of dexamethasone 21-isonicotinate (VorenH Depot TM ) that results in peak dexamethasone concentration 24 hours after administration and sustained serum concentrations as long as 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Lavoie et al could not demonstrate improved lung function in horses with RAO after administration of a leukotriene D 4 antagonist [14]. A more recent study suggested that there is increased leukotriene B 4 and C 4 production in airways of horses affected with RAO which may contribute to infiltration of neutrophils into the lungs and the sustained inflammation associated with RAO [15].…”
Section: Introductionmentioning
confidence: 99%